Insights into Recent Updates on Factors and Technologies That Modulate the Glycemic Index of Rice and Its Products - Tai Van Ngo; Kannika Kunyanee; Naphatrapi Luangsakul (My University, 2023)
Rice is a staple food and energy source for half the world’s population. Due to its quick digestion and absorption in the gastrointestinal tract, rice is typically regarded as having a high or medium–high glycemic index (GI); however, this can vary depending on the variety, nutrient compositions, processing, and accompanying factors. This report included a table of the glycemic index for rice and rice products in different countries, which could give an overview and fundamental information on the recent GI of different rice varieties. In addition, latest updates about the mechanism effects of rice nutritional profiles and processing techniques on GI were also provided and discussed. The influence of state-of-the-art GI regulation methods was also evaluated. Furthermore, the effectiveness and efficiency of applied technologies were also given. Furthermore, this review offered some aspects about the potential nutraceutical application of rice that food scientists, producers, or consumers might consider. Diverse types of rice are grown under various conditions that could affect the GI of the product. The instinct nutrients in rice could show different effects on the digestion rate of its product. It also revealed that the rice product’s digestibility is process-dependent. The postprandial glucose response of the rice products could be changed by modifying processing techniques, which might produce the new less-digestive compound or the inhibition factor in the starch hydrolysis process. Because of the significant importance of rice, this paper also concluded the challenges, as well as some important aspects for future research.
Keywords: Nutraceutical; Digestion; Food composition and properties